Proyecto de Factibilidad para la Implementación de una Empresa dedicada al Servicio y atención de una Estética Canina a domicilio en la ciudad de Loja - Chuquirima Ajila, Jonathan Javier (2017)
The present research work has the purpose of developing the present research work entitled "PROJECT OF FACTIBILITY FOR THE IMPLEMENTATION OF A COMPANY DEDICATED TO THE SERVICE AND ATTENTION OF A CANINE AESTHETICS TO ADDRESS IN THE CITY OF SHOP". Because it can be evidenced that the care and attention of dogs as pets is a problem for their owners due to various factors, especially due to lack of time. For the present project, it has also met the development of the general and specific objectives, proposed in this study. The main objective of this study is to determine the feasibility of the project, based on market, technical, administrative and financial studies. For this purpose, the following methodology was used: In the market study, the size of supply and demand was determined through an analysis that allowed the determination of unsatisfied demand. Subsequent to this the marketing plan was carried out in which the "four p" are established, as they are: product, price, place and promotion. The technician study determined that the company will have an installed capacity of 7,280 services per year, which corresponds to 100% of installed capacity. 5 In the organizational study, legislative, executive, advisory, auxiliary and operational levels were established. For each one, functions have been established depending on the position they use in each position. In the financial study it was determined that a total of $ 36,045.35 dollars is required for the company to start its operation. Through the application of the financial evaluation it was determined that the project is feasible, this through the application of financial indicators such as: Net Present Value with a value of $ 29,500.00 dollars; The Capital Recovery Period, indicates that the investment will be recovered in 2 years, 6 months; The Internal Rate of Return is 39.71%; The Cost Benefit Ratio indicates that for every dollar invested in this company will have a profit of 0.30 cvts and sensitivity analysis the company supports an increase in costs of 11%, and a decrease in revenue of 8.45 %. Finally, the bibliography, the annexes and the index of the project are presented.